The case series of Eisenmenger syndrome and its pregnancy outcome in tertiary care centres of South India - Nathan, Jayalakshmi Meganathan; Thirupathi, Kalaivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
The incidence of the Eisenmenger syndrome (ES) is very rare in the pregnant women, but it has significant association with materno-fetal morbidity and mortality. The prognosis of ES in terms of materno fetal outcomes and neonatal outcomes in the pregnant women is unclear. The main aim of this study is to evaluate the materno-foetal outcome of pregnancy with ES in a tertiary care centre. The case series had been observed in retrospective aspect at 2 tertiary care centres of South India, Government Thiruvarur Medical College and Hospital, Government Villupuram Medical College and Hospital, Tamil Nadu, India over a period of 1 year from 2023-2024. This study analysed the occurrence of ES in the pregnant women with cardiac disease and their materno-foetal outcomes in tertiary care centres of South India. In our study period, 41,718 cases were delivered, in which 6515 cases had cardiac disease, 1105 cases had congenital heart disease. Of these, 6 cases had ES during pregnancy. In our study, ES was noted in 1: 6953 pregnant women, 1:1086 pregnant women with cardiac disease, 1:184 pregnant women with congenital cardiac disease. The mean age was 23.4±0.52 and mean gestational age at delivery was 34±1.25 weeks. The mean pulmonary arterial pressure was 73 mmHg. In our study, 3 cases had preterm deliveries and 1 case had term delivery, 2 cases delivered vaginally, 2 cases had caesarean section and 2 cases had abortions. As per our study, nil maternal mortality reported. For achieving optimum outcomes in the pregnant women with ES, the well-equipped obstetric critical care unit with multidisciplinary approach must be ensured in a tertiary care centre.